Decolonising Restoration and Justice: Restoration in Transitional Cultures - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2000)
Employing perspectives and techniques of comparative contextual analysis, Findlay maintains that restorative justice may be construed as a new form of colonialism, particularly in transitional cultural contexts. Restorative justice initiatives, in this view, tend to locate models of conflict resolution in the contextual customs of indigenous cultures, expropriate them from those indigenous contexts, and subsume them in the state-centered systems of the 'outside' dominant culture. In some instances then, proponents of restorative justice processes have failed to respect the limitations of the models they promote, and they have failed to address the tensions with the systems they seek to replace. Findlay highlights the application of banishment in Western Samoa as an example of such dynamics. In view of all of this, Findlay proposes a reinterpretation of restorative justice as collaborative justice - restoring culturally sensitive custom-based resolutions within and beyond their original contexts.